Effect of Steel Fiber on Plastic Hinge Length of Concrete Columns: Buckingham Theory Application - . Tavio; Bambang Sabariman; Slamet Widodo (Civil Engineering Journal, 2024)
The accuracy of designing the performance of concrete structures nowadays not only depends on the use of standard materials (cement, sand, and gravel) for certain concrete strengths but also on the accuracy of using additional materials for concrete, such as steel fiber. The use of steel fiber not only can improve the performance of concrete structures to behave in a ductile manner but can also form plastic hinges according to design purposes. The design of the axial load of Pa=0.121.Ag.f'c is based on the prediction of the column’s axial capacity. The columns were designed to behave in a flexural manner. As predicted, the lengths of the plastic hinges were found not too long. Controlling the length of plastic hinges in the design of structural concrete members is necessary to avoid excessive displacements. The control is mainly related to the prediction of the plastic hinge length. Thus, in this case, a plastic hinge length formula is required. In the study, the length of the plastic hinges of columns, which are confined with square stirrups and reinforced with steel fiber with Vf = 0%, 0.5%, 1%, 1.5%, and 2%, is proposed. This plastic hinge length formula is proposed after all column test specimens have met the displacement ductility requirement of mD>4, meaning that all test specimens are defined as very ductile. Doi: 10.28991/CEJ-2024-010-05-03 Full Text: PDF